Wayang Santri Sebagai Media Dakwah Dalam Pementasan Ki Entus Susmono - Ibnu Waseu (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Puppet Santri is a form of puppet art used as a medium for Islamic da'wah (propagation). Through this medium, da'wah messages are conveyed by the puppeteer through storylines and puppet dialogues in a straightforward manner, making it easier for the audience to receive the messages without coercion. As a medium of da'wah, Puppet Santri consistently incorporates Islamic teachings encompassing aspects of faith (aqidah), law (shari'ah), and morality (akhlaq). Along with the development of the times and advances in technology in the contemporary era, da'wah media have become increasingly diverse. Therefore, in every performance, Puppet Santri addresses themes that are closely related to societal phenomena and realities, such as heroism (patriotism), loyalty, leadership, marriage, birth, struggles for ownership rights, and the pursuit of knowledge. These themes are presented symbolically, conveying life values intended to serve as guidance for the audience after watching the performance. This study employs qualitative research with a descriptive approach. It examines societal problems and the procedures practiced within communities under specific circumstances, including social relationships, activities, attitudes, and influences in various phenomena. In this context, the researcher seeks to describe and analyze Puppet Santri as a medium of da'wah popularized by Ki Enthus Susmono.